Pendidikan dan Pelatihan Mengenali Kelainan Rongga Mulut dan Cara Pencegahannya - Dipankara, Jackson; Hadrian, Gary; Susanto, Shannon Winnie; Lidwina, Naomi; Riad, Anastasya Muna; Zen, Yuniar; Pakpahan, Alfred; Laksmiastuti, Sri Ratna; Poedjiastoeti, Wiwiek; Kurniawan, Vanesha Jane (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
The oral health promotion program is an effective way to enhance the community's ability to maintain their dental and oral health, provide access to information about dental and oral health, and guide the community toward adopting proper and correct behaviors regarding dental and oral health. The educational and training activities aim to increase the community’s knowledge about oral cavity disorders and their prevention. There were 82 participants from the Paguyuban Umat Senior Wihara Ekaya Arama (PUSA) community who took part in this activity. The training and education were conducted using PowerPoint presentations, videos, and posters as teaching tools. Based on the pre-test and post-test results, there was a noticeable increase in post-test scores, indicating an improvement in participants' knowledge after receiving education and training on oral cavity disorders and their prevention. The conclusion from the education and training activities provided to the PUSA community is that there was an increase in participants' knowledge. It is hoped that these educational and training activities will continue to benefit the community and enhance their ability to maintain dental and oral health.